Factors associated with mask use in New York City neighborhood parks during the COVID-19 pandemic: A field audit study - Lisa Hitch; Marie A. Sillice; Hanish Kodali; Katarzyna E Wyka; Javier Otero Peña; Terry TK Huang (Elsevier, 2022)
Background: Mask use is a cost-effective measure to decrease COVID-19 transmission. Mask mandates intend to increase mask compliance but are often ambiguous when it comes to public outdoor spaces. Methods: We used a field audit study to examine mask use in New York City neighborhood parks during COVID-19. 1453 park visitors were observed in 13 parks during July-August 2020 using a modified and validated park use audit tool (System for Observing Play and Recreation in Communities) that included items on general and proper mask use (i.e., mask covering both nose and mouth). Generalized estimating equation regression was used to determine the association between proper mask use and demographic (sex and age) and behavioral (physical and social activity) variables, while adjusting for community-level covariates. Results: Overall, 39.0% of park visitors used masks (24.4% properly, 14.6% improperly). Females (p = 0.023), adults (p = 0.025), and seniors (p = 0.006) showed higher rates of proper mask use compared to males and younger visitors. Physical and social activity were not significantly associated with proper mask use. Conclusion: There is a need for improved messaging regarding the proper use of masks among males and younger people. This is particularly important for future surges of new COVID-19 variants or other public health crises similar to COVID-19. Future research should focus on developing and evaluating targeted public health messages regarding mask use.